2022
DOI: 10.1002/hed.27181
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of metastatic lymph node ratio over number of node metastases and TNM/AJCC N classification in predicting cancer‐specific survival in medullary thyroid cancer

Abstract: Background: In medullary thyroid cancer (MTC), it is unclear which nodal classification system, metastatic lymph node ratio (MLNR), number of node metastases, or TNM/AJCC N classification, predicts cancer-specific survival best. Methods: Kaplan-Maier analysis of cancer-specific survival after operation at a tertiary center. Results: Included were 505 MTC patients. The spread of the survival curves was greatest after stratification by MLNR (in 0.20 increments), followed by number of node metastases (in 10-node … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…LND correlates with the total LN yield and is a surrogate of adequacy of neck dissection. Several articles have shown that use of the LND allowed investigators to better stratify the prognosis after resection of malignant neoplasms of the head and neck (22,23). However, debate exists about whether the most accurate prognostic factor in PTC patients is the number of positive LNs or the LND.…”
Section: Introductionmentioning
confidence: 99%
“…LND correlates with the total LN yield and is a surrogate of adequacy of neck dissection. Several articles have shown that use of the LND allowed investigators to better stratify the prognosis after resection of malignant neoplasms of the head and neck (22,23). However, debate exists about whether the most accurate prognostic factor in PTC patients is the number of positive LNs or the LND.…”
Section: Introductionmentioning
confidence: 99%